The Effectiveness of Vocabulary Apps in Enhancing the Vocabulary Skills of Pre-University Students: The Case of Memrise - Essafi, Mohamed; Belfakir, Latifa; Moubtassime, Mohammed (Journal of Posthumanism, 2026)
The purpose of this research is to examine the effectiveness of app-based learning for curriculum vocabulary among pre-university students, with Memrise as a case study. The study adopts a quasi-experimental design, including stratified sampling and pre- and post-testing phases. The study participants (n=48) were first randomly sampled from four high schools in Sefrou. The sample was then divided into two groups: an experimental group (n=24) and a control group (n=24). In line with the research design, data was collected using vocabulary tests, both at the outset (pretest) and at the endpoint (posttest) of a semester-long intervention. The gathered data was analyzed using an independent samples t-test. The findings yielded divergent outcomes, with, on the one hand, research hypothesis one indicating a significant performance gap favoring users of Memrise in the vocabulary posttest, and on the other hand, research hypothesis two being rejected, as only four of six vocabulary aspects displayed a significant advantage for Memrise users over non-users of the app. In the end, the study highlights the need for guiding learners to access online resources and use them effectively in their self-mode vocabulary learning practices.